PWE-093 Is cholecystostomy a good alternative treatment for acute cholecystitis in high risk patients?. (22nd June 2015) - Khalifa, E; Papis, D; Nair, A; Prasad, A; Khan, S; Lam, F; Hamady, Z; Shah, J; Marangoni, G
Abstract : Introduction: Cholecystectomy is the treatment of choice for acute cholecystitis whose management in high risk surgical patients could be a difficult dilemma. With the development of interventional radiological skills, percutaneous cholecystostomy (PCS) could represent a less invasive option. Method: This is a retrospective single Centre study; data were collected from our hospital electronic record system. From February 2009 to March 2014 there were 353 patients admitted with acute cholecystitis. Of these 39 were considered high risk for surgery and underwent PCS during their hospital stay. The radiological approach was trans-peritoneal in 29 patients and trans-hepatic in 10 patients. Median follow-up was 19 months. Aim of the study was to assess the outcomes of percutaneous cholecystostomy in high risk patients. Results: There were 27 male (69.2%) and 12 female (30.8%) with mean age of 72 years (range 41–90 yrs). Twenty seven patients had PCS as definitive treatment (group A) and 12 patients as a bridge to cholecystectomy (group B). There were no post-procedures complications. Three patients in group B required conversion to open surgery (25%). Mean length of hospital stay was 15.7 days (group A and B). ITU admission was required for 8 patients (20.5%). Five patients in group A were readmitted once with another episode of cholecystitis after PCS (18.5%), with a median time to readmission of 85 days (3 patients readmitted within 90 days). One patient in group B was readmitted with cholecystitis after 2 years before proceeding to cholecystectomy, and 2 patients were readmitted after cholecystectomy (16.6%) for intra-abdominal collections treated with percutaneous ragiological drainage. Seven patients died (17.9%) as a result of severe biliary sepsis during their index hospital admission. Conclusion: PCS is a safe approach in high risk patients with acute cholecystitis and can provide satisfactory long-term results when cholecystectomy is not a viable option. Disclosure of interest: None Declared.